Réalisation d'un pollinisateur du palmier dattier - Ahmed NOURANI; Ahmed KADRI; Zineldine BENGUIGA; Mokhtar MEHENNI; Ahmed SALEM; Ferhat KACI (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2017)
Several studies have attempted to mechanize the date palm pollination given its importance. Indeed, this work contributes to the enrichment of this topic by providing a new pollination device to date palm growers. This pollinator consists of a powdering device mounted on a telescopic pole. Field tests of this pollinator were conducted in Touggourt and Biskra (Algeria). The date yield obtained with this pollinator was the same as that of the traditional pollination method. The cost of the device was less than the cost of pollinating about 25 palm trees by the traditional method. Moreover, pollination by this device required half the time which was necessary by the traditional method of pollination. With this device, the safety of the farmer is assured since he doesn’t have to climb the palm tree anymore which is also very important. The promising research results obtained testing the developed pollination device makes this pollinator an alternative option for farmers in economic, security and time savings terms. And when the function of this pollinator is based on the dispersion of pollen, we determined that the best percentage pollen / wheat flour was 20%.